Are Tacca leontopetaloides (Linn.) O. Kuntze Mini-tuber Growth Affected by Media Composition and Tuber Size? - Aziz, Sandra A.; Susanto, Rendi (Department of Agronomy and Horticulture, IPB University, 2015)
Tacca (Tacca leontopetaloides (Linn.) O. Kuntze) is a tropical plant that is widely used for its starch in some countries as well as a medicinal plant. Tacca has advantages as it can grow on sand in tropical seashore areas and rain forests. Farmers in Madura Island Indonesia cultivated tacca by using mother tubers as propagules and harvest the daughter tubers, but no studies have been conducted on the growth of mini tubers and their cultivation. The purpose of this study was to find the best combination of planting media and the size of mini tuber for growing tacca. The experiment was set in a completely randomized block design with two factors and three replications. The planting media are sand : rice-hull charcoal : cow manure (1:1:1 v/v), soil : sand : cow manure (1:1:1 v/v), soil : rice-hull charcoal : cow manure (1:1:1 v/v), and soil : cow manure (1:1 v/v);mini-tuber weight are1-5 and 5.1-20 g. The result showed that Polynesian arrowroot grow best on sand : rice-hull charcoal : cow manure (1:1:1 v/v) and rice-hull charcoal : cow manure (1:1 v/v) media. Both propagules sizes can be used, but plants from large mini-tuber had better growth and produced larger mother and daughter tubers. Key words: mini tuber, parent tuber, Polynesian arrowroot, organic media planting, secondary tuber